CINCO NOVAS ESPÃ‰CIES DE COPIFORÃNEOS DO BRASIL (ORTHOPTERA â€“ TETTIGONIIDAE) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2015)
CINCO NOVAS ESPÃ‰CIES DE COPIFORÃNEOS DO BRASIL (ORTHOPTERA â€“ TETTIGONIIDAE)